Experimental Analyses on T-junction Geometry in Two Phase Flow - Tengku Bazli, Tengku Muhamad Nazmi (IRC, 2018)
T-junction piping is broadly use in the application of flow separation in two phase fluid flow system. This type of pipe geometry is commonly seen at the offshore production pipeline in oil and gas industry and is used as partial separator of two phase flow before the feed fluid enter the separation equipment. This partial process helps in increasing phase separation efficiency as it splits both phase through different arm in it channel. This project conducted experiment on the effect of phase separation and its relationship with regular and reduced T-junctions with diameter ratio of 1, 0.6, 0.5, 0.27 and four different velocity combinations of air superficial velocity of 0.12 - 1.12 m/s and water superficial velocity of 0.4 - 0.53 m/s. All of the chosen velocities combinations produced slug flow of the two phase flow inside the T-junctions. This study concluded that reduced T-junction, higher superficial velocity of water increase phase separation efficiency.